Epidemiological Indices of COVID-19 Viruses in Countries with High-incidence: A Descriptive and Comparative Analysis - Javad Javan-Noughabi; Sayed Ali Mousavi; Seyed Yaser Hashemi; Ahmad Faramarzi; Farshad Bahrami Asl; Hamidreza Shabanikiya (Shiraz University of Medical Sciences, 2023)
Background: Coronavirus disease 2019 (COVID-19) has posed an unusual threat to global health. Up to May 26, 2021, according to a report by the World Health Organization (WHO), 167.01 million cases, and 3.47 million deaths were reported. This study aimed to estimate and compare epidemiological indices of COVID-19 in high-incidence countries.Methods: We conducted a descriptive and comparative analysis intending to examine the epidemiological indices of COVID- 19 in high-incidence countries, using the data published by the WHO until May 17, 2021. We calculated the incidence and mortality rate per 1,000,000 inhabitant-day at risk daily, weekly, and overall, using person-day as the denominator.Results: The fatality rate in 14 countries was about 1.94%. The highest fatality rate was acquired in Italy (2.99%), followed by the United Kingdom (2.86%) and Iran (2.79%). The lowest value on the fatality rate was in Turkey and India, at 0.88% and 1.1%. The highest incidence rate was reported in the USA (207 cases per 1,000,000 person-day), followed by France (190), Poland (171), and Argentina (167). The highest mortality rate for the whole period was extracted in Brazil (4.60 death per 1,000,000 population-day), and the lowest rate happened in India (0.42).Conclusion: Until May 17, 2021, COVID-19 has affected about 117.6 million patients and caused 2.3 million deaths in 14 highincidence countries. This study shows that a specific pattern of COVID-19 has been observed in every country.